Chemical Analysis of Wastewater Produced in an Industrial Enterprise (Eurasian Scientific Herald, 2023)
In this article, the chemical composition of wastewater produced in industrial enterprises, in particular, the composition of wastewater produced in the process of obtaining ultramarine pigment produced at the joint venture "Sofitel" LLC located in the industrial area of Jizzakh city, was studied using the mass spectrometry method. results are reported.